Computation by inverse causality: A universal principle to produce symbols for the external reality in living systems - Nakajima, Toshiyuki (BioSystems, 2022)
How can a living system escape the solipsistic self-making process? This problem has been ignored in mainstream biology. This study seeks a reasonable mechanism by which a living system produces symbols that signify external states. To this end, the inverse causality model proposed in previous studies was theoretically improved by refining the core concepts. Inverse causality is an epistemic principle operating in a subject system to produce symbols internally, signifying the past states of the external reality hidden to the subject. Inverse causality yields an important theorem for a system to produce symbols for external states. It asserts that if a system changes from state x to y1 in some instances, and from x to y2 in others (y1 ≠ y2), then x ⟼ y1 produces a symbol that signifies one external state, and x ⟼ y2 produces a different symbol for another state. These symbols are embodied as the states of the system components. The model postulates the equivalence principle in the subject-reality relationship, asserting that inverse causality is equivalent to causality in the external view. Living systems operate with inverse causality using biological devices called measurers, which include membrane receptors, second messengers, and molecular switches in cells, and neurons in multicellular organisms. A measurer is a medium of symbols signifying external states. Biological subsystems functioning as measurers are ubiquitous and essential in contemporary living systems for adaptation to their environments in particular ways by manipulating the symbols they produce. By the inverse causality operation, living systems can reduce the uncertainty of events and manage the probability distribution of future events favorable to survival and reproduction. Due to this function, their measurer systems were sophisticated and diversified in evolution. In philosophy and science, there has been endless debate between determinism and indeterminism. However, surprisingly, contemporary living systems use the inverse causality operation (ICW) to adapt to their environments, which is logically equivalent to the causal principle of determinism.